Pemanfaatan educaplay dalam pembelajaran matematika di kelas III-D MI Bustanul Ulum kota Batu - Qorin, Najwa Aliva (Maliki Interdisciplinary Journal, 2025)
Mathematics learning at the elementary school level often faces challenges related to students’ interest and understanding of the material. The use of interactive learning media is one of the solutions to improve learning effectiveness. Educaplay, as an educational game-based e-learning platform, offers various features that capture students’ attention and encourage active participation in the learning process. This article explores the use of Educaplay in teaching Mathematics to third-grade students at MI Bustanul Ulum Kota Batu. Through an engaging and interactive approach, Educaplay not only facilitates more creative concept understanding but also enhances students’ motivation to learn. This article also examines the alignment between student characteristics and the effectiveness of digital media, as well as the teacher’s role in selecting appropriate learning strategies.